1998
DOI: 10.1180/002646198547891
|View full text |Cite
|
Sign up to set email alerts
|

Parasibirskite, a new mineral from Fuka, Okayama Prefecture, Japan

Abstract: Parasibirskite, with the ideal formula Ca2B2O5·H2O, is a new mineral species found at Fuka, Okayama Prefecture, Japan. It is a polymorph of sibirskite, CaHBO3, and occurs as subparallel aggregates of tabular crystals up to 40 × 20 × 3 µm in size. Associated minerals are takedaite, olshanskyite, sibirskite, frolovite and calcite. The mineral is white, and has a weak pearly luster. Optically, the mineral is biaxial positive, α 1.556(2), β 1.593(2), γ 1.663(2) (λ 589 nm). The Vickers microhardness of aggregates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…At the Fuka mine, calcium borate minerals such as olshanskyite, nifontovite (Kusachi and Henmi, 1994), takedaite , frolovite , and parasibirskite (Kusachi et al, 1998) have been found in an irregular body up to 3 m long and 2 m wide in the crystalline limestone near the gehlenite spurrite skarns. During the present study, a new occurrence of the calcium borate minerals was also found at the same mine, where nifontovite and pentahydroborite occur abundantly as composite minerals in an irregular body up to 7 m long and 3 m wide in the crystalline limestone in the vicinity of the skarns.…”
Section: Occurrencementioning
confidence: 99%
“…At the Fuka mine, calcium borate minerals such as olshanskyite, nifontovite (Kusachi and Henmi, 1994), takedaite , frolovite , and parasibirskite (Kusachi et al, 1998) have been found in an irregular body up to 3 m long and 2 m wide in the crystalline limestone near the gehlenite spurrite skarns. During the present study, a new occurrence of the calcium borate minerals was also found at the same mine, where nifontovite and pentahydroborite occur abundantly as composite minerals in an irregular body up to 7 m long and 3 m wide in the crystalline limestone in the vicinity of the skarns.…”
Section: Occurrencementioning
confidence: 99%
“…A series of calcium borate and calcium borate hydroxide minerals such as takedaite, sibirskite, parasibirskite, uralborite, nifontovite, olshanskyite, frolovite, and pentahydroborite were discovered at Fuka, Okayama Prefecture, Japan Kusachi et al, , 1995Kusachi et al, , 1997Kusachi et al, , 1998Kusachi et al, , 1999Kusachi et al, , 2000. These are hydrothermal alteration products of takedaite, and the concentration of H 2 O varies with the formation temperature, as discovered by Hart and Brown (1962) from the hydrothermal synthesis of calcium borate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These are hydrothermal alteration products of takedaite, and the concentration of H 2 O varies with the formation temperature, as discovered by Hart and Brown (1962) from the hydrothermal synthesis of calcium borate compounds. Parasibirskite, CaHBO 3 , a new mineral, is a dimorph of sibirskite that was first reported in Fuka by Kusachi et al (1998). The crystal structure of sibirskite was determined using Monte Carlo calculations by Miura and Kusachi (2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten new minerals were discovered from this occurrence. They are bicchuite (Henmi et al, 1973), fukalite (Henmi et al, 1977), oyalite (Kusachi et al, 1984), henmilite (Nakai et al, 1986), clinotobermerite (Henmi and Kusachi, 1992) morimotoite , kusachiite (Henmi, 1995), takedite , parasibirskite (Kusachi et al, 1998), and okayamalite (Matsubara et al, 1998). Five of these new minerals are calcium boro silicates.…”
Section: Introductionmentioning
confidence: 99%